Non-ulcerated necrotizing sialometaplasia may mimic a salivary gland tumor - Patrícia Maria Fernandes; Erika Graf Pedroso; Alan Roger Santos-Silva; Pablo Agustin Vargas; Márcio Ajudarte Lopes (University of São Paulo, 2021)
Necrotizing sialometaplasia (NS) is a benign, self-limiting inflammatory entity that mainly affects the minor salivary glands located in the hard palate. Classically, NS is characterized as a nodule that evolves to a central ulcer. The most widely recognized triggering factor is an ischemic event. The diagnosis becomes a challenge in non-ulcerated NS cases which is essential to rule out the possibility of salivary gland tumors, especially the malignant ones. Here, we presented a case of a 32-year-old male patient with a 1-month complaint of a painful, slightly elevated erythematous area on the hard palate. Incisional biopsy was performed, and NS was diagnosed based on histopathological and immunohistochemical analyses. Clinicians should be aware of and consider NS as a differential diagnosis of minor salivary gland tumors, particularly when it presents as a non-ulcerated clinical aspect.